Remote assessment of physical fitness via videoconferencing: a systematic review - Thorsten Klein; Annette Worth; Claudia Niessner; Anke Hanssen-Doose (BMC Sports Science, Medicine and Rehabilitation)
Abstract Physical fitness is a critical marker of overall health across all age groups, influencing longevity and quality of life. This systematic review assessed the use of remote physical fitness assessments, a crucial adaptation during the COVID-19 pandemic that broadened access to health monitoring outside traditional settings. The review included 35 studies, covering various age groups and health conditions, and evaluated 48 physical fitness tests across eight physical fitness components. Balance, muscular strength, and endurance were the most frequently assessed, with tests like the 30-second sit-to-stand (30s-STS) showing strong validity, reliability, and feasibility for remote use. However, the study population was mainly adults and older adults, with nearly no focus on children, revealing a significant gap in research for younger populations. Additionally, the review identified gaps in assessing components such as body composition, reaction time, and agility, which are crucial for a comprehensive assessment of physical fitness. These gaps underscore the need for further research and development of reliable and valid remote assessment tools. The findings of this review emphasize the importance of standardizing remote physical fitness assessments to ensure their validity, reliability, and feasibility making them effective tools for health monitoring across diverse populations and settings.